2013
DOI: 10.3947/ic.2013.45.2.184
|View full text |Cite
|
Sign up to set email alerts
|

The Long and Short Incubation Periods ofPlasmodium vivaxMalaria in Korea: The Characteristics and Relating Factors

Abstract: BackgroundThe cases of Plasmodium vivax malaria in Korea are mixed with long and short incubation periods. This study aims to define clinico-epidemiologic chracteristcs of Plasmodium vivax malaria in Korea.Materials and MethodsWe selected the civilian cases infected with P. vivax malaria in Korea from the epidemiological investigation data of 2001 to 2010, whose incubation periods could be estimated. The long and short incubation periods were defined by duration of infection and onset time, and the cases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Kim et al (2013) obtained the similar results with a shorter mean incubation period than Nishiura et al (2007). An estimate of transmittable prevalence with the incubation periods of Kim et al (2013) will change the results.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Kim et al (2013) obtained the similar results with a shorter mean incubation period than Nishiura et al (2007). An estimate of transmittable prevalence with the incubation periods of Kim et al (2013) will change the results.…”
Section: Discussionmentioning
confidence: 68%
“…Kim et al (2013) obtained the similar results with a shorter mean incubation period than Nishiura et al (2007). An estimate of transmittable prevalence with the incubation periods of Kim et al (2013) will change the results. This possibility is partly covered in the confidence interval computations in Sections 2.3 and 4 by considering the uncertainty of the survival functions that originated from the estimated pdf of Nishiura et al (2007).…”
Section: Discussionmentioning
confidence: 68%
“…A study in Korea found median short incubation of P. vivax malaria at 18 days and median long incubation at 332 days. 5 So our case would be extreme if considered to be imported. Each case was passed on from the hospital to public health authorities to investigate this further and treat the local surrounding area as appropriate.…”
Section: Resultsmentioning
confidence: 92%
“…These two groups of institutionalized patients had mosquito-transmitted infections with defined exposure dates and complete follow-up [ 12 ]. Data for the infections with long-latency (extended incubation periods) were extracted from three published studies that involved two unrelated temperate strains; one involved drug prophylaxis [ 14 ], two were observational studies with inferred exposure dates [ 15 , 16 ], and all include extensive interval censoring in reported event times.…”
Section: Methodsmentioning
confidence: 99%